Simulation of The Temperature Profile of The Curing Process of Thick Carbon Fiber Laminates Using The Age Algorithm - Amna Amna; Ahmad Kamal bin Zulkifle; Norma Alias; Norhalena Mohd. Nor; Noreliza Abu Mansor; Ishak Hashim (STEKOM PRESS, 2020)
This paper determines by simulation the temperature profiles of a thick carbon fiber/epoxy laminate during its cure process. The one-dimensional model of heat transfer is solved by using a finite difference numerical scheme. In the process, the same physical and thermal properties of materials used by ZhanSheng et al. are employed. The temperature is calculated through a judicious formulation and application of the Alternating Group Explicit (AGE) iterative method developed by Evans and Sahimi. A fourthorder Runge Kutta method is applied for the cure. The AGE scheme proves to be a viable iterative method with respect to stability, efficiency and rate of convergence.